Globalization and growth : - Vietor, Richard H. K. (Thomson Delmar Learning, 2005)
This text contains cases developed for use in teaching international political economy at the Harvard Business School. They represent the major developmental trajectories that have defined the recent history of economic growth. These cases empirically describe the strategies of China, India, Japan, Mexico, South Africa, Poland and the Czech Republic, Europe and the United States. As a group, these countries represent more than half the world’s population and nearly two-thirds of its gross domestic product. The cases are as much political and institutional as they are economic and are based on Harvard’s way of teaching analytical methodology for managers called "country analysis," which is a method of identifying the economic performance, social and political context, and national development strategy of a country or region. It also assesses each strategy in terms of its effects on the performance and its fit with context.